Tinjauan: Efektivitas Metode Sonikasi Dalam Ekstraksi Senyawa Bioaktif Dari Limbah Kulit Buah - safitri, mutiara (TAPE : Jurnal Teknologi Hasil Pertanian, 2025)
Plant-based food waste such as fruit peels contain various high-value bioactive compounds that have the potential to be used as functional ingredients in the food and pharmaceutical industries. One of the innovative methods used to extract these compounds is Ultrasound-Assisted Extraction (UAE), which is known to be efficient, environmentally friendly, and able to maintain the quality of active compounds. This article aims to systematically review the effectiveness of UEA in extracting bioactive compounds from fruit peels such as, mangosteen, pear, and kiwi. A literature study was conducted by analyzing five main articles in the period 2015-2025. The results of the study showed that UEA was able to increase the yield, total phenolic and flavonoid content, and antioxidant activity significantly compared to conventional methods. The effectiveness of UEA is greatly influenced by the type of solvent, sonication time, temperature, ultrasonic power, and sample-solvent ratio. Therefore, UEA is a sustainable technology that promises to utilize food waste into high-value products. Keywords : bioactive compounds, food waste, fruit peels, ultrasound-assisted extraction.